2022
DOI: 10.54028/nj202221210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Responsive Strategies and Adaptive Behavior of Occupants on Thermal Comfort in Indoor Environments of Vernacular Architecture: A Review of Necessities and Goals

Abstract: This study addresses the goals, reasons, and necessities of analyzing the effects of climate responsive strategies and adaptive behavior on thermal comfort in the indoor environments of vernacular architecture. For this purpose, 86 studies were reviewed, including 71 studies about climate responsive strategies and 15 others about adaptive behavior in vernacular architecture and dwellings that were carried out between 2000 and 2018. The research methodology included a statistical survey and analysis of necessit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…This amount of difference in energy consumption between traditional and modern buildings in northern Iran and the amount of near-zero summer consumption of rock-cut buildings for cooling shows the low level of energy consumption in vernacular buildings of Iran. Further [ 23 ], studied the summer thermal comfort of traditional buildings in eastern Iran, situated in a warm and arid climate, across six different villages by using questionnaires. They found that the passive natural ventilation system employed in these buildings can contribute to comfort during 51 % of hot days throughout the year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This amount of difference in energy consumption between traditional and modern buildings in northern Iran and the amount of near-zero summer consumption of rock-cut buildings for cooling shows the low level of energy consumption in vernacular buildings of Iran. Further [ 23 ], studied the summer thermal comfort of traditional buildings in eastern Iran, situated in a warm and arid climate, across six different villages by using questionnaires. They found that the passive natural ventilation system employed in these buildings can contribute to comfort during 51 % of hot days throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, most of the studies have focused on assessing the thermal comfort of residents in traditional buildings across various climates by employing questionnaires and comparing them with the experiences of users in different structures. The findings suggest that occupants of traditional buildings experience higher levels of comfort during warm seasons compared to the residents of modern buildings in the same conditions [ [23] , [24] , [25] , [26] ]. Furthermore, some have focused on modeling influential factors on thermal comfort, such as natural ventilation and structure orientation, based on ASHRAE standards in traditional buildings across different climates.…”
Section: Introductionmentioning
confidence: 99%